Le miroir haïtien de Ben Fountain - Françoise Palleau-Papin (IdeAs)
This paper examines how Ben Fountain’s short stories depict interpersonal relationships between the characters, not unlike voodoo possession which depersonalizes, borrowing from Haitian Creole amongst other narrative means. Setting up Haiti as a mirror to the United States, Fountain examines how the characters relate to one another and to money, and imagines new forms of exchange and new ways of being in the world, “Thinking-of-the-Other” as in the philosophy of Emmanuel Lévinas.